Isometric handgrip training enhances cognitive performance through improved reaction time and accuracy / Intan Shahira Farisha Sa’odi ... [et al.]. - Sa’odi, Intan Shahira Farisha; Linoby, Adam; Sazali, Razif; Zulqarnain, Muhammad; Haziq, Amrun; Md Yusoff, Yusandra (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study examines the acute effects of short-term interval handgrip exercise on cognitive function. By comparing reaction time, accuracy, and heart rate responses between exercise and control groups, we aim to determine whether isometric exercise enhances cognitive performance [1]. Addressing a research gap, this study explores the potential of handgrip exercise as a low-impact cognitive enhancement tool for individuals unable to engage in dynamic exercises. Sixteen FSR recreational students participated in the study, divided into an exercise and a control group. Both groups completed cognitive tasks (Stroop and Go/No-Go). The exercise group performed isometric interval handgrip exercise at 25% submaximal effort, while the control group rested. Post-exercise, both groups repeated cognitive tasks. Accuracy, reaction time, and heart rate were recorded. Data were analyzed using independent t-tests, paired t-tests, and Pearson correlation.